Comprehensive analysis of juvenile idiopathic arthritis patients’ immune characteristics based on bulk and single-cell sequencing data - Liu, Mubo; Gong, Yadong; Lin, Mu; Ma, Qingqing (Frontiers in Molecular Biosciences, 2024)
The pathogenesis of juvenile idiopathic arthritis (JIA) is strongly influenced by an impaired immune system. However, the molecular mechanisms underlying its development and progression have not been elucidated. In this study, the computational methods TRUST4 were used to construct a T-cell receptor (TCR) repertoire and B-cell receptor (BCR) repertoire from the peripheral blood of JIA patients via bulk RNA-seq data, after which the clonality and diversity of the immune repertoire were analyzed.Results: Our findings revealed significant differences in the frequency of clonotypes between the JIA and HC groups in terms of the TCR and BCR repertoires. This work identified specific V genes and J genes in TCRs and BCRs that could be used to expand our understanding of JIA. After single-cell RNA analysis, the relative percentages of CD14 monocytes were significantly greater in the JIA group than in the control group. Cell-cell communication analysis revealed the significant role of the MIF signaling pathway in JIA.In conclusion, this work describes the immune features of both the TCR and BCR repertoires under JIA conditions and provides novel insight into immunotherapy for JIA.